Vehicular emissions and air quality on the roads - Goh, Oliver Koon Jeow. (2011)
In order to maintain/improve Singapore’s air quality, this project endeavours to assess the impact of vehicle emissions on the air quality. This research was carried out in four separate phases to achieve this objective.